Computer-interfacing design for real time signal classification using fuzzy / Mohd Hairey Abdul Halim - Abdul Halim, Mohd Hairey (2005)
This thesis is aim to classify and display the real time signal in frequency through personal computer (PC). The process involved the used of AI (Artificial Intelligence) technique. Software based on MATLAB Fuzzy Toolbox and MATLAB Simulink will be used to develop the fuzzy logic. The real time input signal based on the ultrasound frequency ranges generated by the signal generator will be insert to the fuzzy logic controller through the computer-interfacing system that will be built and designed based on RS-232 communication. The output will be displayed through the personal computer based on the classification of the frequency signal set in the membership function.